Prescribing Patterns of Antihypertensive Medications in Low- and Middle-Income Countries: A Systematic Review. (January 2021) - Arshad, Verda; Samad, Zainab; Das, Jai; Almas, Aysha; Rashid, Nouman; Virani, Salim S.; Bloomfield, Gerald S.; Jafar, Tazeen H.; Ahmed, Bilal
Hypertension is highly prevalent, but its pharmacological management has not been well evaluated in low- and middle-income countries (LMICs). This review examined the prescribing patterns of antihypertensives in LMICs. Data were extracted from a total of 26 studies spanning the time period 2000 to 2018. In 10 studies, calcium channel blockers (CCBs) were the most frequently prescribed medication for managing hypertension (range = 33% to 72%); in six studies, renin angiotensin system (RAS) blockers (range = 25% to 83%); in five studies, diuretics (range = 39% to 99%); and in five studies, β-blockers (BBs; range = 26% to 49%) were the most commonly prescribed antihypertensive medications. Prescribing sedatives and sublingual administration of captopril for controlling hypertension was also reported in 3 studies. Only 10 studies presented their findings in light of national or international guidelines. This review calls for further antihypertensive utilization and dispensation studies and a better understanding of clinician's perception and practice of hypertension management guidelines in LMICs.